The soul of education : helping students find connection, compassion, and character at school - Kessler, Rachael, 1946- (Association for Supervision and Curriculum Development, 2000)
Rachael Kessler shows how can educators and parents of diverse backgrounds can come together to find ways to invite soul into schools without violating the separation of church and state or the deeply held beliefs of families and students.